Human Development Report 2019 - Programme des Nations Unies pour le Développement (United Nations, 2019)
Inequalities in human development are a roadblock to achieving the 2030 Agenda for Sustainable Development. They are not just about disparities in income and wealth. They cannot be accounted for simply by using summary measures of inequality that focus on a single dimension. And they will shape the prospects of people that may live to see the 22nd century. The 2019 Report explores inequalities in human development by going beyond income, beyond averages and beyond today. It asks what forms of inequality matter and what drives them, recognizing that pernicious inequalities are generally better thought of as a symptom of broader problems in a society and economy. It also asks what policies can tackle those drivers—policies that can simultaneously help nations to grow their economies, improve human development and reduce inequality. The e-book for this publication has been converted into an accessible format for the visually impaired and people with print reading disabilities. It is fully compatible with leading screen-reader technologies such as JAWS and NVDA.